Demographic and Well-Being Predictors of Regular and Long-term Practice of Argentine Tango in a Multicultural Sample of Practitioners. - Santana, Rita; Gouveia, Maria; Carvalheira, Ana (American Journal of Dance Therapy, 2017)
The practice of Argentine tango has experienced exponential growth all over the world, and several studies have revealed its positive outcomes on physical health. The present study aims to analyze demographic, well-being, and other psychological variables associated with the regular and long-term practice of Argentine tango. Participants included 524 men and women from 52 countries ( Mean = 42.4; SD = 11.52; Range = 18-77). A multiple regression analysis was carried out designating the frequency of attendance at milongas as the dependent variable. Among women ( n = 334), age, relationship situation, flourishing, and flow, emerged as significant predictors. Older and non-committed women, with a low level of flourishing, and a high level of flow were more likely to report a high frequency of tango practice. Among men ( n = 190), relationship situation, flourishing, flow, and positive affects emerged as significant predictors. Non-committed men, with a low level of flourishing, a high level of flow, and a high level of positive affects were more likely to report a high frequency of tango practice. Another multiple regression analysis was conducted using the length of participants' experience dancing tango as the dependent variable. Older and committed women with a high level of flow were more likely to report a pattern of long-term tango practice. Older men with a high level of flow were also more likely to be long-term practitioners of tango. These results raise questions about the potential effects of tango dancing on participants' well-being.